Association between sagittal abdominal diameter-to-height ratio and arteriosclerotic cardiovascular disease among the United States adults: A cross-sectional study - Xi Gu; Dou Tang; Yan Xuan; Ying Shen; Leiqun Lu (Preventive Medicine Reports, 2024)
Objectives: Abdominal obesity is recognized as a significant determinant of Arteriosclerotic cardiovascular disease (ASCVD), with sagittal abdominal diameter (SAD) being considered a more precise indicator of visceral fat. Nevertheless, the association between SAD and ASCVD remains unexplored in large-scale general-population studies. Methods: The study included 11,211 participants aged 20 to 80 from the National Health and Nutrition Examination Survey. Logistic regression models were utilized to evaluate the association between the SAD-to-height ratio (SADHtR) and ASCVD. Subgroup analyses based on age categories, sex, diabetes, and hypertension were conducted to assess result robustness. Results: The median SADHtR value was 0.13 (0.12–0.15), and 1,006 cases (7.46 %) of ASCVD were recorded. Multivariable models showed that each standard deviation increase in SADHtR was positively associated with higher odds of ASCVD (OR 1.48, 95 % CI 1.36–1.62 in model 1; OR 1.41, 95 % CI 1.28–1.54 in model 2; OR 1.18, 95 % CI 1.08–1.30 in model 3). Comparing the first quartile of SADHtR to the second to fourth quartiles, positive associations with ASCVD were observed in models 1 and 2. However, in model 3, only the fourth quartile of SADHtR remained statistically significant (OR 1.58, 95 % CI 1.17–2.15), with all p-values for the trend being less than 0.05. No interactions were found in the subgroup analyses. Conclusion: This study demonstrates a positive association between SADHtR and ASCVD in the general adult population of the United States. Our findings indicate that SADHtR, especially when ≥ 0.155, could be a valuable metric for assessing the risk of ASCVD.